Financial Literacy for Generation Z: Strategies for Developing an Economically Intelligent and Self-Reliant Generation at SMA Negeri 1 Gowa. - Andriani, Shadry; Devi Nugraha, Putu Ananda; Nur Wahyuningsih, Andi; Abdur Rabb, Ahmad Faqhruddin; Ngoyo, Muh. Fardan (Outline Publisher, 2025)
The rapid development of digital technology has brought significant changes to financial systems and consumption behavior patterns, including among teenagers. Generation Z, as active users of technology, faces challenges in managing their finances wisely amid the ease of access to digital financial services. The Community Service Program (PKM) entitled “Financial Literacy for Generation Z: Strategies to Build an Economically Smart and Independent Generation” was conducted at State Senior High School 1 Gowa with the aim of enhancing students’ knowledge and awareness of responsible personal financial management. This activity employed an educational participatory approach through interactive lectures, discussions, financial planning simulations, and financial games that actively engaged students. The results showed an improvement in students’ understanding of the importance of expense tracking, budget planning, and the wise use of digital wallets. Students also began to grasp the concepts of investment and the risks associated with the use of “pay later” features, which are increasingly popular among youth. Through this program, students were able to distinguish between needs and wants, develop saving habits, and cultivate discipline and responsibility in managing their finances. Overall, the program successfully instilled the fundamental values of forming an Economically Smart and Independent Generation youth who are rational, visionary, and possess integrity in facing the challenges of the digital economy.